Therapeutic efficacy of omalizumab in children with moderate-to-severe allergic asthma combined with chronic sinusitis - Chong, Weikun; Li, Hailang; Wang, Juan (Frontiers in Allergy, 2023)
Background Omalizumab has been approved for treating moderate-to-severe asthma in children aged over 6 years. Its application to asthmatic children with other allergic diseases has been rarely explored. The present study aims to explore the therapeutic efficacy of omalizumab in children with moderate-to-severe allergic asthma combined with chronic sinusitis. Methods The clinical data of children diagnosed with moderate-to-severe allergic asthma combined with chronic sinusitis and treated with omalizumab between September 2020 and April 2022 were retrospectively analyzed. Lung function indexes such as Childhood Asthma Control Test (C-ACT) scores, fractional exhaled nitric oxide (FeNO), and forced expiratory volume in the first second (FEV1) percent predicted (FEV1%pred), small airway function indexes, and the clinical symptoms of chronic sinusitis were analyzed. Results A total of 26 children were observed for 16 weeks. After 16 weeks of omalizumab treatment, the significantly increased C-ACT scores (15.57 ± 3.25 points vs. 24.98 ± 5.21 points, F = 15.7112, P < 0.001) and decreased FeNO (31.55 ± 15.57 ppb vs. 19.86 ± 9.80 ppb, F = 4.4265, P = 0.0022), compared with those at baseline, were suggestive of well-controlled symptoms of asthma and improved lung function. FEV1%pred and FEV1/forced vital capacity (FVC) ratio (the ratio of the forced expiratory volume in the first 1 s to the forced vital capacity) increased after omalizumab treatment, although no significant differences were detected (P = 0.9954 and 0.9382, respectively). Peak expiratory flow (PEF) percent predicted (PEF%pred) and forced expiratory flow at 75% of FVC (FEF75%), 50% of FVC (FEF50%), and 25%–75% of FVC (FEF25%–75%) significantly increased after omalizumab treatment (P = 0.0477, <0.001, <0.001, and <0.001, respectively). Visual analog scale scores significantly decreased after omalizumab treatment (6.40 ± 2.98 points vs. 0.85 ± 0.40 points, t = 27.2419, P < 0.001), suggesting alleviation in the clinical symptoms of chronic sinusitis. Conclusion In this study, it was found that omalizumab can effectively alleviate clinical symptoms and improve lung function and quality of life in children with moderate-to-severe allergic asthma combined with chronic sinusitis.